Analysis of the Mudharabah Contract in the Perspective of Islamic Fiqh and Its Implementation in Sharia Banking Practice - gama pratama; M Frendi Dian Santana; Amanah Amanah (Prodi Perbankan Syariah Fakultas Ekonomi dan Bisnis Islam Universitas Islam Bunga Bangsa Cirebon, 2025)
The Mudharabah Agreement is a form of cooperation agreement between two parties, namely the mudharib (fund manager) and the shahibul mal (capital owner), where the profits are divided based on the previous agreement. Transparency, trust, and active involvement of both parties are the keys to the success of this contract. Mudharabah is often used in the context of Islamic finance to support the principle of risk and reward sharing. In its implementation, the Mudharabah contract reflects the principles of justice and economic sustainability in accordance with Islamic sharia values.